Do connections with buy-side analysts inform sell-side analyst research? - Gjergji Cici; Philip B. Shane; Yanhua Sunny Yang (University of Cologne, Centre for Financial Research (CFR), 2017)
We hypothesize that connections with buy-side analysts provide a sell-side analyst with private information generated by the buy-side that enhances the quality of sell-side research. We proxy for these connections with the number of stocks at the intersection of stocks held in the portfolios of institutional investors and followed by the sell-side analyst. The larger this intersection, the more opportunities the sell-side analyst has to interact with institutional investors. We proxy for the research quality of the sell-side analyst with the relative accuracy of her earnings forecasts. We find that such connections enhance the accuracy of earnings forecasts, but up to a point of diminishing returns. Additional tests rule out that the observed association is due to reverse causality.
Keywords: 330